PERBANDINGAN ANTARA DUA PENDEKATAN NORMALISASI DATA HINGGA KONDISI FOURTH NORMAL FORM (4NF) - Michael Iskandar (Center for Economic Studies Universitas Katolik Parahyangan, 2003)
Data normalization is a technique used to create databases that are able to store data in an effective and efficient manner. This, in turn, will ensure the integrity of the data contained within those databases. The process of normalizing a database from completely unnormalized to its ultimate form is a gradual one, and in practical terms this is commonly thought of as necessitating at least four steps, each of which is marked with a specific